(untitled) (Bangladesh Journal of Botany, 2023)
Korean pine is a monoecism gymnosperm that predominantly exists as both female and male. Due to the absence of a model organism reference genome, high-throughput sequencing was used to analyze the candidate unigenes of tissue and organ development. This was performed in the tissues of microstrobilli (Ms), needles (Ne), and mixed buds (Mb) of the Korean pine to mine for genes related to bud differentiation and flowering. Overall, 26.32 Gb of clean data comprising 26972 annotated unigenes were obtained. Out of these, 26323 (97.59%) were annotated in the NR database based on sequence homology. Twenty-four GO terms and 30 candidate unigenes related to the formation or development of flowers, needles, buds, and pollens were found by GO enrichment analysis. Bangladesh J. Bot. 52(2): 243-252, 2023 (June)